2013
DOI: 10.1186/1748-5908-8-137
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted strategy using mobile technology to assist rural primary healthcare doctors and frontline health workers in cardiovascular disease risk management: protocol for the SMARTHealth India cluster randomised controlled trial

Abstract: BackgroundBlood Pressure related disease affected 118 million people in India in the year 2000; this figure will double by 2025. Around one in four adults in rural India have hypertension, and of those, only a minority are accessing appropriate care. Health systems in India face substantial challenges to meet these gaps in care, and innovative solutions are needed.MethodsWe hypothesise that a multifaceted intervention involving capacity strengthening of primary healthcare doctors and non-physician healthcare w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Interventions aimed at incorporating patient-centered NCD management within existing community-based health efforts, traditionally oriented towards infectious disease and malnutrition, may prove to be both cost-effective and transformative [30]. New technologies such as m-health (mobile phone-based health technology) may allow for implementation of patient-centered care directly in rural communities [31, 32]. As with any new health system intervention, the ideal program should be low-cost, require minimal input of new resources, culturally acceptable, and scalable.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions aimed at incorporating patient-centered NCD management within existing community-based health efforts, traditionally oriented towards infectious disease and malnutrition, may prove to be both cost-effective and transformative [30]. New technologies such as m-health (mobile phone-based health technology) may allow for implementation of patient-centered care directly in rural communities [31, 32]. As with any new health system intervention, the ideal program should be low-cost, require minimal input of new resources, culturally acceptable, and scalable.…”
Section: Discussionmentioning
confidence: 99%
“…129 In addition, a multifaceted strategy using mobile technology to assist rural primary healthcare doctors and frontline health workers in CVD risk management has been developed and was implemented in 18 primary health centers and 54 villages in rural Andhra Pradesh involving ≈15 000 adults aged ≥40 years at high CVD event risk. 127 The results of these studies have the potential to inform policy on scalable strategies to improve the efficiency of the health system in managing CVD. The trial identified no effect of the health promotion strategy on the primary knowledge outcome.…”
Section: Improving Efficiency Of Carementioning
confidence: 99%
“…All the studies supported NPHWs by training them for two to six days, followed by re-training where required. 14, 54, 55 Some studies facilitated task redistribution by using mHealth technology, 14, 56 whereby NPHWs used electronic decision support tools to screen individuals in the community and link them to hypertension care. Process and interim evaluations have identified that the main barriers to task-redistribution include resistance from other health professionals; increasing NPHW workload due to additional tasks; complexity of training materials; health system-related issues such as non-availability or non-functioning BP machines, poor drug supply, lack of physician availability for referral; regulatory restrictions including the inability to prescribe medications; and low remuneration of NPHWs.…”
Section: Task Redistributionmentioning
confidence: 99%